Dense Breast Legislation in the United States: State of the States - Dehkordy, Soudabeh Fazeli; Carlos, Ruth C. (Journal of the American College of Radiology, 2013)
Limitations of screening mammography in patients with dense breasts combined with the significant increased risk for breast cancer have made the issue of dense breasts a matter of great concern in recent years, leading to advocacy for policy change and legislation. Dense breast notification legislation requires direct patient notification of mammographic results indicating the presence of dense breast tissue. The aim of this study was to summarize the state of dense breast notification legislation across the country. The general intent of dense breast notification legislation is to increase awareness of dense breasts and encourage patients to discuss the clinical issues with their physicians. It was first enacted in Connecticut in 2009, and since then, 27 other states have passed, rejected, or considered dense breast notification legislation. At the federal level, a bill was introduced in October 2011, but it was not enacted. There are significant differences in the language of the laws from state to state that complicate implementation. Furthermore, legislated recommendations for possible additional testing are often unaccompanied by legal provisions for insurance coverage, which potentially results in unequal access.